Susceptibility of Some Corylus avellana L. Cultivars to Xanthomonas arboricola pv. corylina - Webber, John Bryan; Wada, Sugae; Stockwell, Virginia O.; Wiman, Nik G. (Frontiers in Plant Science, 2021)
Bacterial blight of hazelnut (Corylus avellana L.) is caused by Xanthomonas arboricola pv. corylina (Xac). In the past, bacterial blight has been a key disease impacting the Oregon hazelnut industry where 99% of the United States hazelnut crop is grown. The disease is re-emerging in young orchards, as acreage of newly released hazelnut cultivars rapidly increases. This increase in hazelnut acreage is accompanied by renewed interest in developing control strategies for bacterial blight. Information on susceptibility of hazelnut cultivars to Xac is limited, partially due to lack of verified methods to quantify hazelnut cultivar response to artificial inoculation. In this research, Xac inoculation protocols were adapted to two hazelnut growing environments to evaluate cultivar susceptibility: in vitro tissue culture under sterile and controlled conditions, and in vivo potted tree conditions. Five hazelnut cultivars were evaluated using the in vitro inoculation protocol and seven hazelnut cultivars were evaluated using the in vivo inoculation protocol. Under in vitro conditions there were severe bacterial blight symptoms on each cultivar consistent with those seen in the field, but no significant differences in the susceptibility of the newly released cultivars were observed compared to known Xac-susceptible cultivar (‘Barcelona’). Under in vivo conditions the proportion of necrotic buds were significantly higher in ‘Jefferson’ and ‘Dorris’ compared to all of the other tested cultivars, including ‘Barcelona’. The symptom progression seen in vivo mirrored the timing and symptom progression of bacterial blight reported from field observations. The in vitro conditions significantly reduced the amount of time required to measure the inoculation efficiency compared to the in vivo environment and allowed for greater replication. Further studies on the effects of Xac can use the results of these experiments to establish a dose-response model for bacterial blight, a wider range of germplasm can be tested under in vitro conditions, and management strategies that can be evaluated on large populations of new cultivars using the in vivo methods.